2014
DOI: 10.1166/jnn.2014.7973
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Mediated Tunneling Transport Between Carbon Nanotubes in Nanocomposites

Abstract: Electron transport in nanocomposites has attracted a good deal of attention for some time now; furthermore, the ability to control its characteristics is a necessary step in the design of multifunctional materials. When conductive nanostructures (for example carbon nanotubes) are inserted in a non-conductive matrix, electron transport below the percolation threshold is dominated by tunneling and thus the conductive characteristics of the composite depends heavily on the characteristics of the tunneling current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(4) was chosen to be 0.6 Å -1 , which has been calculated for PAN [76]. First, the effect of two related properties, waviness and aspect ratio, is studied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(4) was chosen to be 0.6 Å -1 , which has been calculated for PAN [76]. First, the effect of two related properties, waviness and aspect ratio, is studied.…”
Section: Resultsmentioning
confidence: 99%
“…Various experimental studies have shown that functionalization [40,[71][72][73][74], chirality [71,75], aspect ratio [17,62,71], host matrix material [11,76], CNT dispersion in the matrix [17,35,[37][38][39]71,74,77], relative alignment [17,65,75] and other processing variables can all have a significant impact on the electrical properties of the composite.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…For simplification, in order to calculate the conductance of the investigated volume element at a given deformation, we assumed the inner resistance of MWCNTs to be negligible compared to the contact resistance between MWCNTs or between the MWCNT and the electrode. 34,35 The relative conductance (the ratio of conductance for a selected degree of deformation to conductance of non-deformed volume) was obtained using Kirchhoff's circuit laws for the grid of unit contact resistances and unit input and output electrical currents flowing through upper and lower faces of the ''inner'' volume. The principle of contact grid formation is illustrated in Figure 5.…”
Section: Numerical Partmentioning
confidence: 99%